A comparative study of psychiatric comorbidity and quality of life between tension-type headache patients and healthy controls - Jaiswal, Arpit; Sharma, Ekaansh; Sharma, Chinar; Sharma, Simran; Utkarsh, Kumar; Ali, Ramjan (Asian Journal of Medical Sciences, 2022)
Background: Headache is a health disorder that affects a large proportion of the world population, resulting in a huge economic burden. Nearly half the world’s population has a history of current headache disorder. Its prevalence is reported to vary over a wide range from 1.3% to 65% in men and 2.7% to 86% in women. It is responsible for 7.2 million years of life lived with disability. The present study was planned to study the prevalence and clinical impact of psychiatric comorbidity and quality of life among patients with tension-type headache (TTH) in a North Indian population. Aims and Objectives: To assess the psychiatric comorbidity and quality of life among the patients of Tension type Headache and compare them with healthy controls. Materials and Methods: Patients presenting with complaints of headache and healthy individuals without complaints of headache were included in the study. A total of 100 patients were studied that were presenting in tertiary care hospital. Patients were subjected to a semi-structured interview, diagnosis made by ICHD-3 for TTH, and psychiatric comorbidity was detected by Mini-International Neuropsychiatric Interview applied to both patients and controls. Results: Psychiatric morbidity was diagnosed in 90% of cases and only 9% of controls. Among cases with psychiatric morbidity, generalized anxiety disorder (28%) was the most common, followed by major depressive disorder (MDD) (27%), panic disorder (12%), social phobia (11%), agoraphobia (6%), alcohol dependence (4%), and substance dependence (2%), respectively. On the other hand, among controls, 7% had MDD and 2% had alcohol dependence. Statistically, a significant difference was found between the two groups (P<0.001). The quality of life of TTH patients with psychiatric comorbidity was significantly lower as compared to that of TTH patients without psychiatric morbidity. Conclusion: The findings of the study showed a much higher prevalence of psychiatric comorbidity among TTH patients as compared to matched healthy controls. The quality of life of TTH patients was highly impaired, presence of psychiatric comorbidity made the quality of life of affected patients even worse.